2018
DOI: 10.1016/j.ymthe.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Improves the Therapeutic Efficacy of Human Bone Marrow Mesenchymal Stem Cells via RAD51

Abstract: Human embryonic stem cell-derived mesenchymal stem cells (hE-MSCs) have greater proliferative capacity than other human mesenchymal stem cells (hMSCs), suggesting that they may have wider applications in regenerative cellular therapy. In this study, to uncover the anti-senescence mechanism in hE-MSCs, we compared hE-MSCs with adult bone marrow (hBM-MSCs) and found that hepatocyte growth factor (HGF) was more abundantly expressed in hE-MSCs than in hBM-MSCs and that it induced the transcription of RAD51 and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
(63 reference statements)
0
24
0
Order By: Relevance
“…Tivantinib inhibited hUC-MSC-upregulated autophagy via activating the PI3K/AKT/mTOR signaling pathway. Lee et al (37) revealed that HGF is more abundantly expressed in human embryonic stem cell-derived mesenchymal stem cells than in adult bone marrow-derived MSCs (hBM-MSCs). However, HGF-treated hBM-MSCs exhibited significantly improved therapeutic efficacy by promoting telomere lengthening and inducing mitochondrial DNA replication and function.…”
Section: Discussionmentioning
confidence: 99%
“…Tivantinib inhibited hUC-MSC-upregulated autophagy via activating the PI3K/AKT/mTOR signaling pathway. Lee et al (37) revealed that HGF is more abundantly expressed in human embryonic stem cell-derived mesenchymal stem cells than in adult bone marrow-derived MSCs (hBM-MSCs). However, HGF-treated hBM-MSCs exhibited significantly improved therapeutic efficacy by promoting telomere lengthening and inducing mitochondrial DNA replication and function.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte growth factor could promote the differentiation of stem cells, which may be associated with the activation of Wnt signaling [181]. Another study found that this hepatocyte growth factor significantly promotes the viability of embryo-derived mesenchymal stem cells and prevents its senescence, which is associated with transcription of RAD51 [182]. All of the above growth factors have an impact on the proliferation and differentiation of stem cells.…”
Section: Cell-adhesive Ligandmentioning
confidence: 98%
“…Therefore, lentivirus-or adenoassociated virus has been widely used for stable and prolonged expression of HGF in vivo. Previous studies have shown that BMSCs overexpressing HGF could significantly enhance hepatocyte regeneration, inhibit apoptosis, and reverse the progression of liver fibrosis [20,21]. UTMD was proved to be an effective method to deliver genes and drugs by acoustic cavitation effects generated by the interaction of ultrasound and microbubbles [22,23].…”
Section: Discussionmentioning
confidence: 99%